Promoting Social cum Racial Integration in South Africa by Making an African Language a National Senior Certificate Pass Requirement. Sibe simunye at last! - (:unkn) unknown (My University, 2010)
The need for making an African language compulsory at matric, to give fair chance to all, transform the education system and society at large in a country with a legacy of division by language and race.
Keywords: African Research